Study on factor affecting student’s performance towards English for Mathematics: a case study in SMK Bandar Putra, Segamat Johor - Sabtu, Muhamad Azrol; Rosli, Norhayati (2008)
The implementation of Science and Mathematics in English as a policy start on 2003 by Malaysia government. The rationale of the implementation is because the usage of English in international level is very important. Moreover, this policy is to strengthen the ability of students in Malaysia in penetrating the global workforce. The study examines the affecting students’ performance toward the implementation of this policy. Among the factor we look into are demographic, student’s attitude, teachers and school commitment, level of English mastering among students and the environment itself. There are three objective of this study that is first to identify the level of student’s attitude, school and teachers commitment, English mastering among students and environment surrounding students towards English for Mathematics, second is to analyze whether these all factors will contribute or affect students’ performance in Mathematics paper in PMR and the last objective is to identify which factors is contribute most to students’ performance in Mathematics. Based on the findings, is can be conclude that only three factors can affect students’ performance in Mathematics that is student’s attitude, English mastering among students’ and environment surrounding students. While for the most factors that will affect students’ performance in Mathematics is student’s attitude.